Development of pH Sensitive Microspheres of Esomeprazole Magnesium Using Natural Gums for Zollinger-Ellison Syndrome - Balamuralidhara, V.; M. Pramod Kumar, T.; Vishal Gupta, N.; Moin, Afrasim; V. Gangadharappa, H. (Drug Delivery Letters, 2012)
The objective of the present research work was to develop pH sensitive mucoadhesive microspheres employing Natural gums for Esomeprazole magnesium used in the treatment of Zollinger-Ellison syndrome. Esomeprazole magnesium (EM), a proton pump inhibitor (PPI) is used as a model drug. For this purpose, EM microspheres were prepared by spray-drying technique using Karaya gum (KG) and Xanthan gum (XG) as mucoadhesive control release polymers and glutaraldehyde as a crosslinking agent. Hydroxylpropyl methylcellulose acetate succinate (HPMCAS), which is soluble above pH 6.0 was used for the coating of mucoadhesive microspheres. Absence of chemical interactions between drug, polymers and crosslinking agent after the production of microspheres was confirmed by Fourier transform infrared spectroscopy (FTIR). The results of Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) indicated a molecular level dispersion of esomeprazole magnesium in the polymer matrix. Microspheres obtained were spherical as confirmed by scanning electron microscopy. The prepared formulations exhibited a good mucoadhesive strength, which was determined by in vitro falling film technique and was compared with ex vivo studies. Also the microspheres exhibited a good swelling index and high percentage of drug entrapment. The in vitro release showed no drug release in pH 1.2. While in pH 6.8 microspheres showed the maximum release of more than 85% in 12 h. The release best followed peppas model and showed super case II transport kinetics. It may be concluded that pH sensitive microspheres of esomeprazole magnesium may be designed for oral administration for the treatment of Zollinger-Ellison syndrome.
Keywords: FT-IR